Hierarchy of hybrid materials. Part-II: The place of organics-on-inorganics in it, their composition and applications - Song, Junnan; Vikulina, Anna S.; Parakhonskiy, Bogdan V.; Skirtach, Andre G. (Frontiers in Chemistry, 2023)
Hybrid materials or hybrids incorporating organic and inorganic constituents are emerging as a very potent and promising class of materials due to the diverse but complementary nature of their properties. This complementarity leads to a perfect synergy of properties of the desired materials and products as well as to an extensive range of their application areas. Recently, we have overviewed and classified hybrid materials describing inorganics-in-organics in Part-I (Saveleva, et al., Front. Chem., 2019, 7, 179). Here, we extend that work in Part-II describing organics–on-inorganics, i.e., inorganic materials modified by organic moieties, their structure and functionalities. Inorganic constituents comprise of colloids/nanoparticles and flat surfaces/matrices comprise of metallic (noble metal, metal oxide, metal-organic framework, magnetic nanoparticles, alloy) and non-metallic (minerals, clays, carbons, and ceramics) materials; while organic additives can include molecules (polymers, fluorescence dyes, surfactants), biomolecules (proteins, carbohydtrates, antibodies and nucleic acids) and even higher-level organisms such as cells, bacteria, and microorganisms. Similarly to what was described in Part-I, we look at similar and dissimilar properties of organic-inorganic materials summarizing those bringing complementarity and composition. A broad range of applications of these hybrid materials is also presented whose development is spurred by engaging different scientific research communities.